Effects of hemodynamic conditions and valve sizing on leaflet bending stress in self‐expanding transcatheter aortic valve: An in vitro study. Issue 7 (25th February 2020) - Stanová, Viktória; Zenses, Anne‐Sophie; Thollon, Lionel; Kadem, Lyes; Barragan, Paul; Rieu, Régis; Pibarot, Philippe
Abstract: Transcatheter aortic valve (TAV) replacement has become a viable alternative to surgery for high and intermediate risk patients with severe aortic stenosis. This technology may extend to the younger and lower risk patients. In this population, long‐term durability of the TAV is key. Increased leaflet mechanical stress is one of the main determinants of valve structural deterioration. This in vitro study aims at evaluating leaflet bending stress (LBS) in the self‐expanding TAV for different valve sizes, stroke volumes (SV), and degrees of valve oversizing (OS). Three different sizes (23, 26, and 29 mm) of CoreValve (CV) were tested on a pulse duplicator in annulus size ranging from 17 to 26 mm. Leaflet bending stress and bending of the leaflet coaptation line in diastole pinwheeling index (PI) were measured using high‐speed camera imaging (1000 images/s). For each given CV and annulus size, geometric orifice area (GOA) increased significantly with OS ( P < .001) and SV ( P = .001). LBS decreased with increasing prosthesis size and aortic annulus (AA) size while increasing with SV ( P < .03). The largest value of peak LBS (3.79 MPa) was obtained with the CV 23 mm in AA of 17 mm (%OS = 35%), SV 90 mL and the smallest value (0.99 MPa) for the CV 29 mm in AA of 26 mm (%OS = 12%), SV 30 mL. On multivariable analysis, LBS increased independently with larger OS, smaller AA size and higher SV. The PI increased with decreasing AA size and increasing OS. Moderate valve OS, such as generally used for transcatheter aortic valve implantation, is associated with increased LBS during valve opening and closing, especially in small annuli. Hence, TAV OS may negatively impact long‐term valve durability.